Adsense Mobile dan Respon Pengguna Smartphone: Intrusiveness dan Irritation - Muhammad Wali (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2017)
The increasing use of smartphones and the advent of Adsense Mobile Service (Admob) to deliver the marketing message has not been followed by empirical evidence of their effectiveness. This research aims to test the influence of smartphone users against Adsense Mobile (Admob) intrusiveness toward consumer irritation, the attitude on advertising, consumer attitudes towards products that are presented, and consumer purchasing intentions against ads that appear on a smartphone. Testing the effectiveness of service Adsense Mobile (Admob) is based on the phenomenon of the increasing use of smartphones to deliver marketing messages on consumers in a different demographic. Preliminary research framework built upon Advertising Avoidance Theory. For data collection, self-administered survey conducted by applying the purposive sampling and involving 70 respondents who are domiciled in Aceh and never play a smartphone application. The results showed that more consumers feel that ads appearing on Smartphones, Adsense Mobile (Admob) interfere with their comfort (intrusive) and the higher feelings of anger (irritation) that form on smartphone users or application. The influential consumer negative feelings of anger in the formation of attitude on Adsense Mobile (Admob) and stance on the product being advertised. The better the attitude on Adsense Mobile (Admob) effect on the increasingly positive attitude of consumers to the product being advertised. So did the increasingly positive attitude of smartphone users on the product appeared, the more positive the user's intention also to buy the product being advertised. Interestingly, the attitude on the Adsense Mobile Smartphones (Admob) has no effect against the intention to buy. The results of this study contribute to marketing practitioners who use Adsense Mobile Service (Admob) as media placement in their advertising strategies.